Testing an egg yolk supplemented diet on boars to aid in sperm adaptation at 5°C. (3rd September 2015) - Casas, Isabel; Miller-Lux, Yvonne; Osborne, Betty; Bonet, Sergi; Althouse, Gary C.
Abstract: In many species, extended semen can be stored at low temperatures to slow bacterial growth. However, boar semen performs poorly at temperatures below 15°C and this poses unique challenges, as it is not easy to maintain a constant 15–19°C during shipment. Some extenders have been formulated with egg yolk for storage at 5°C but the addition of egg yolk is not applicable in the majority of commercial operations. The purpose of this study was to evaluate if boar dietary supplementation with powdered egg yolk imparts any protective effects on sperm quality when stored at 15°C and 5°C for up to 11 days in a conventional extender. Ten boars were fed a commercial diet with the addition of 0.11Kg of powdered egg yolk for 10 weeks. Ejaculates collected on weeks 4, 6, 8, and 10 were processed for storage at both 15°C and 5°C and compared with ejaculates from boars fed a standard diet. Throughout an 11-day storage period, sperm quality was assessed including several motility and morphologic parameters and select plasma membrane properties (fluidity, integrity, and triacylglycerol content). Linear regression models were used to describe effects of treatment, storage day, week and temperature on all sperm parameters. Overall, there were minimal beneficial effects of egg yolk treatment on sperm quality parameters. Sperm from egg yolk supplemented boars did have a slower decline in viability and plasma membrane fluidity than that observed in the control sperm when stored at 5°C ( p < 0.001). Additionally, there was an increase in total morphologic abnormalities in sperm from egg yolk fed boars compared to controls at week 10 ( p < 0.001). In conclusion, the results of this study do not support a significant benefit to sperm quality or resistance to cold storage when feeding a 10-week dietary supplementation of 0.11Kg powdered egg yolk to crossbred boars.